The Effect of Noni Fruit on the Blood Pressure of Elderly Patients at TPMB (Midwife Independent Practice) T, Purwakarta Regency, Indonesia - Hani Nurhayati; Bunga Anggita Sagia (Archives of The Medicine and Case Reports, 2023)
The higher the life expectancy of the elderly, the more problems that arise in the elderly due to the aging process and degenerative problems that reduce the body's resistance. Hypertension is one of the leading causes of premature death worldwide and hypertension kills nearly 8 billion people every year worldwide. This study aimed to determine the effect of noni fruit on reducing blood pressure in the elderly in TPMB T, Purwakarta Regency, Indonesia. This study is experimental research with a one group pre-post-test approach and uses primary data, namely in the form of blood pressure measurements of research respondents. A total of 30 research subjects participated in this study, where the research subjects met the inclusion criteria. This study shows that the intervention of giving noni fruit extract is effective in lowering blood pressure. There was a decrease in blood pressure after administering noni fruit extract and it was stated to be statistically different, p<0.05. In conclusion, there is an effect of administering noni fruit extract on the blood pressure of elderly patients with hypertension at TPMB T, Purwakarta Regency, Indonesia.